Epilepsy in primary cerebral tumors: The characteristics of epilepsy at the onset (results from the PERNO study – Project of Emilia Romagna Region on Neuro‐Oncology). (4th October 2013) - Michelucci, Roberto; Pasini, Elena; Meletti, Stefano; Fallica, Elisa; Rizzi, Romana; Florindo, Irene; Chiari, Annalisa; Monetti, Cinzia; Cremonini, Anna Maria; Forlivesi, Stefano; Albani, Fiorenzo; Baruzzi, Agostino; et al.
Summary: Purpose: To present new information on the semiology and short‐term evolution of seizures associated with primary brain tumors (PBTs) in a prospective study. Methods: This study is a section of the PERNO study – Project of Emilia Romagna Region on Neuro‐Oncology, the main aim of which is to collect prospectively all cases of PBTs occurring in the Emilia‐Romagna region, northeast Italy (3, 983, 346 population) from January 2009 to December 2011, to allow epidemiologic, clinical, and biomolecular studies. The epilepsy section of the PERNO study included all the patients who experienced seizures, either as first symptom of the tumor or appearing during the course of the disease. Each patient was interviewed by the referring neurologist with a specific interest in epilepsy. The patients who entered the study were followed up with visits on a quarterly basis. Key Findings: We collected 100 cases with full clinical, neuroradiologic, and pathologic data. The majority (79%) had high grade PBTs (glioblastoma in 50 cases), whereas the remaining patients had low‐grade gliomas, mostly localized in the frontal (60%), temporal (38%), and parietal (28%) lobes. Seizures were the first symptom of the tumor in 72 cases. Overall, the initial seizures were tonic–clonic (48%) (without clear initial focal signs in more than half of the patients), focal motor (26%), complex partial (10%), and somatosensitive (8%). The majority of cases (60%) had isolated seizures or a low seizure frequency at the onset of the disease, whereas a high seizure frequency or status epilepticus was observed in 18% and 12% of cases, respectively. Ninety‐two patients underwent surgical removal of the tumor, which was either radical (38%) or partial (53%). Seven patients underwent only cerebral biopsy. In the 72 patients in whom seizures were the first symptom, the mean time to the surgical treatment was 174 days, with a significant difference between high grade (95 days) and low grade (481 days) gliomas. At the time of our first observation, the majority of patients (69%) had already undergone surgical removal, with a mean follow‐up of 3 months after the procedure. Overall, 39 patients (56%) were seizure free after tumor removal. The good outcome did not depend on presurgical seizure frequency or tumor type, although there was a trend for better results with low‐grade PBTs. Significance: These data provide evidence that seizures are strictly linked to the tumoral lesion: They are the initial symptom of the tumor, reflect the tumor location and type, are usually resistant to antiepileptic treatment, and may disappear after the treatment of the lesion.